Deflection of a railway reinforced concrete slab track: Comparing the theoretical results with experimental measurements. (1st September 2016) - Giannakos, Konstantinos
Highlights: Twinblock concrete sleepers' cracks appeared with deterioration of track's geometry. Literature's methods resulted in actions justifying sporadic appearance of cracks. A 20 years research on railway matters, in Greece (OSE), led to results. A new mathematical approach of the actions due to the Non-Suspended Masses is cited. This method is verified by comparison to German measurements on Rheda Slab Track. Abstract: A model of a railway track is presented and a theoretical analysis is performed for the case of a ballastless or slab track section, in a High-Speed line ( V > 200 km/h). In this approach the existing theoretical semi-analytic methods are applied, as cited in the German, French, American literature, as well as the Giannakos (2004) method. This method is valid for speeds in the domain under the critical speed of wave propagation along the rail and it has already been verified for the case of ballasted track, in the case of extended cracking of the sleepers (over 60% of their total number on track). The Rheda Sengeberg slab track type has been in operation, in the Athens–Thessaloniki axis, since 2004; for this slab track type measurements in the German railway network have been published. In this investigation, the Giannakos (2004) method is applied in the slab track section too. A sensitivity analysis is performed for different values/qualities of the stiffness coefficient of the subgrade. The measured deflections, on a Rheda Sengeberg slab track section in Germany, are compared to the results of the theoretical method Giannakos (2004). The probability of occurrence which gives results almost coinciding with the measurements is determined. Conclusions are drawn in relation to the stiffness variation of the subgrade, and its influence on deflection.